What does the future hold for the information associations? A panel with the Presidents of ASIS&T, Alise, and the Chair of iSchools Consortium. Issue 1 (1st February 2019) - Given, Lisa M.; Julien, Heidi; Oh, Sam; Shankar, Saguna
ABSTRACT: This panel will explore how information associations can maintain engagement and relevance at a time when academic disciplines are evolving, when institutional and personal budgets face increasing pressures, and as we strive to connect across a broad global footprint. The panel brings together the leaders of three information science associations – the President of the Association for Information Science and Technology, the President of the Association for Library and Information Science Education, and the Chair of the iSchools' Consortium – to discuss the issues their associations face currently.